Study on Creativity Potential of Scheduled Cast Students With Ref to Five Sub-Tests of Language Creativity: Exploring the Creativity Potential of Scheduled Cast Students (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Fluency is theability of person to produce number of relevant and unrepeated ideas. Relevanceis judged on the basis of the appropriateness of the response when consideredin relation to the test problem and an unrepeated idea is one which has beenexpressed only once under given problem.